Holocene monsoon climate documented by oxygen and carbon isotopes from lake sediments and peat bogs in China: a review and synthesis - Zhang, JW; Chen, FH; Holmes, JA; Li, H; Guo, XY; Wang, JL; Li, S; Lu, YB; Zhao, Y; Qiang, MR (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
There has been much recent debate about Holocene climate variation in the monsoon region of China, especially the temporal pattern of variations in precipitation, the time-transgressive nature of the Holocene precipitation maximum, and the extent to which variations in regions influenced by the Indian Summer Monsoon (ISM) and the East Asian Summer Monsoon (EASM) have been synchronous. We summarize and compare carbonate oxygen-isotope records (delta O-18(carb)) from ten lakes within the present-day ISM region. We discuss their paleoclimate significance considering the present-day moisture source, isotopic composition of precipitation and the hydrological setting. The delta O-18(carb) records are controlled mainly by the isotopic composition of lake water, which in turn is a function of regional Precipitation/Evaporation (P/E) balance and the proportion of precipitation that is monsoon-derived. We normalized the delta O-18(carb) data and used these records to generate an integrated moisture index. This index, along with oxygen-isotope records from speleothems and carbon-isotope records (delta C-13(org)) from peats within the monsoon region, suggests that Holocene climate was broadly synchronous across the monsoon region and, within the limits of accuracy of the existing age models, provides no strong evidence for previously-proposed anti-phasing of the ISM and the EASM. Stable-isotope records from lake sediments and peat bogs have excellent potential for providing high-quality paleoclimate data for monsoon Asia, and complement high-resolution speleothem sequences, which are only found in certain localities. (C) 2011 Elsevier Ltd. All rights reserved.